1983
DOI: 10.1177/002076408302900102
|View full text |Cite
|
Sign up to set email alerts
|

Life Events and Depression in Transit Populations

Abstract: Undesirable recent life events in the period of three months preceding primary depressive illness were studied in two Arabian Gulf countries: Qatar (235 patients) and Kuwait (164 patients). Transit population patients, who come to these countries from employment, differ from native patients in the significant predominance of work as a source of recent life events. The difference is discussed in relation to the existential committments and attitudes to work among native and transient populations. Intergeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our findings negated this hypothesis. Moreover, it did not support the conclusions of McIntire et al (1973) (quoted by El-Islam, 1974) that counterattacking aggressive attitudes towards those attempting suicide favoured recidivism in parasuicidal adolescents. Table 3 Social Readjustment Scores for Repeaters and Non-repeaters The preponderance of family problems as a major precipitating factor of the index parasuicide in a greater number of repeaters than non-repeaters in this investigation tallies with findings of studies elsewhere (Buglass et al 1974;Myers, 1982).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Our findings negated this hypothesis. Moreover, it did not support the conclusions of McIntire et al (1973) (quoted by El-Islam, 1974) that counterattacking aggressive attitudes towards those attempting suicide favoured recidivism in parasuicidal adolescents. Table 3 Social Readjustment Scores for Repeaters and Non-repeaters The preponderance of family problems as a major precipitating factor of the index parasuicide in a greater number of repeaters than non-repeaters in this investigation tallies with findings of studies elsewhere (Buglass et al 1974;Myers, 1982).…”
Section: Discussionmentioning
confidence: 68%
“…The risk of death is known to be greater in repeated suicide attempts than at the first time (Lonnquist, 1977;~ancroft et al 1977) and there is an immediate relationship between parasuicide and life events (Paykel, 1975). El-Islam (1974) reported from Qatar that parasuicide was most frequently carried out in association with an acute situational distress and inter-generational conflict. Emara et al (1987) found parasuicide patients accounted for 3 % of acute medical admissions in Kuwait i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These areas were selected because of their prominence in clinical material wherever attitude conflicts were implicated in patients' presentation and symptomatology (ElIslam 1974(ElIslam , 1976(ElIslam , 1979El-Islam et al 1983). Traditional attitudes enforce obedience and respect of older and male members of the family, favour arranged marriages (especially cousin marriage), and undervalue women's education, restricting their role to marriage and mothering.…”
Section: Methodsmentioning
confidence: 99%